Housing Affordability Stress among the Middle-Income (M40) Group in Johor Bahru - Azizah, Ismail; Siti Nur Adila, Mamat; Wilson Rangga, Anthony Jiram (Malaysian Institute of Planners, 2023)
A house as a place of residence plays an important role towards sustainable development and in improving the wellbeing of the population. The issue of housing, especially the supply and demand of low and low-medium cost housing in cities, rising house prices, quality of housing as well as housing stress has shown that housing is a critical issue that must be addressed. Housing stress usually refers to financial constraints, the reason for the inability to manage the cost of home ownership and housing expenses. Yet financial burden is not the only factor that can contribute to housing stress. There are two types of housing stress, namely physical and emotional factors that may impact negatively on the lives of residents. This paper discusses the affordability housing stress among the middle-income group (M40) that may contribute to housing stress basedon a survey of 100 residents of the M40 group in Johor Bahru. The paper discusses the ability of households to rent or buy a house by considering affordable prices, the ability to repay financing, and sufficient income to meet the basic needs of life and a household.